Your Goals, My Goals, Our Goals: The Complexity of Coconstructing Goals with Learners in Medical Education. Issue 4 (8th August 2019) - Farrell, Laura; Bourgeois-Law, Gisele; Buydens, Sarah; Regehr, Glenn
Abstract: Phenomenon : Despite a long-standing recognition of the importance of learning goals in feedback, there has been relatively little research on how to address mismatches between learner goals and preceptor goals in medical education. Our study addresses this gap by reporting on challenges and strategies around goal coconstruction as identified by clinical educators who were learning and attempting to implement a goal-oriented feedback approach in their own teaching contexts. Approach : We employed a qualitative, design-based research methodology to study how 5 clinician educators incorporated goal-oriented feedback into their teaching practice. Participants attended workshops on goal-oriented feedback and reflective writing. They then narratively reflected over a 6-month period on their attempts with goal-oriented feedback and shared these reflections in periodic facilitated group discussions. Themes were developed using iterative thematic analysis of group discussions and individual exit interviews. Findings : Participants identified several benefits of goal setting in all environments. They perceived improved rapport with learners and developed empathy for the vastness of learner goals. However, they experienced several struggles especially when learner and preceptor goals did not match. These included (a) how to address learner goals that were not easily amenable to a coconstruction, (b) how to coconstruct goals while actively running a clinical practice, and (c) how to remain learner centered while raising preceptor goals based on perceived gaps. Insights : Mismatches between learner and preceptor goals are inevitable and frequent. Preceptors must find ways to coconstruct goals with learners in various learning environments. That said, in enacting goal-oriented feedback, preceptors are effectively using feedback throughout the teaching and learning interaction to coconstruct the learning environment, resulting in improved rapport with learners and emphasizing why it is important to focus feedback around goals.